Assessment of Bone Mineral Density in Nonalcoholic Steatohepatitis Cirrhosis (Bangladesh Journal of Nuclear Medicine, 2019)
Background: Cirrhosis is characterized by diffused hepatic fibrosis and nodule formation that can occur at any age. It has significant morbidity and mortality. Worldwide common causes of cirrhosis are viral hepatitis (hepatitis B virus and hepatitis C virus), prolonged excessive alcohol intake and nonalcoholic fatty liver disease (NAFLD). Progression of chronic liver disease (CLD) and deterioration of liver function are associated with various hepatic complications. Hepatic osteodystrophy is an important extrahepatic manifestation of advanced liver disease with features of classical osteoporosis and an increased risk for fractures. The objective of the study to assess the bone mineral density (BMD) by duel energy x-ray absorptiometry (DEXA) in patients with nonalcoholic steatohepatitis (NASH) cirrhosis of liver. Patients and Methods: A cross sectional observational study was carried out at National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Bangabandhu Sheikh Mujib Medical University (BSMMU) campus, Dhaka, from July, 2016 to June, 2017. This study included the diagnosed cases of NASH cirrhosis patients presented at outpatient or inpatient department of Hepatology of BSMMU. For measurement of the BMD dual energy x-ray absorptiometry (DEXA) scan was performed by DMS Strator DR Bone densitometer at NINMAS.  BMD were measured at lumbar vertebrae L1-L4 and both the femoral neck. Analysis of data from DEXA was computerized and completely automated (software 3DXA, Medix DR.)  Results: A total of 54 participants was included and among them 27 were cirrhotic patients (cirrhotic group) & 27 were non-cirrhotic patients with healthy liver (non-cirrhotic group). The age range of the patients was 40-70 years in both groups. Male to female ratio was 1:1.45.  The mean age was 56.3 ± 6.7 years in cirrhotic group and 55.0 ± 6.3 years in non cirrhotic group. In cirrhotic group, 22 (66.7%) patients had low BMD and five (23.8%) patients had normal BMD. In non-cirrhotic group, 11 (33.3%) patients had low BMD and 16 (76.2%) patients had normal BMD. The difference was statistically significant (p < 0.05) between two groups. Multivariate logistic regression analysis was done to see the effect of multiple independent variables (age, menopause and cirrhosis) on dependent variable (low BMD). In cirrhotic patients odds ratio (OR) was 1.961 (95% CI 0.110 to 25.893) which implies cirrhotic patients had 1.961 times greater chance to develop low BMD than non cirrhotic patients keeping all other factors in fixed level. Conclusion: Hepatic osteodystrophy is an important extrahepatic complication of cirrhosis. NASH cirrhosis is found among elderly people and female. Osteoporosis is common in aged people and menopausal female. But in this study it was observed that a NASH cirrhosis patient is highly significant risk factor for low BMD (osteopenia and osteoporosis) other than aged persons and menopausal females. So, special measures and monitoring should be taken regarding osteoporosis in NASH cirrhotic patient to reduce subsequent morbidity.Bangladesh J. Nuclear Med. 21(1): 16-20, January 2018